Determinant Performance of Islamic Equity Funds in Indonesia - Alif Khuwarazmi Maulana Julendra; Dwi Marlina Wijayanti; Slamet Haryono (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
Financial risk tolerance is a crucial factor affecting the growth of Islamic Equity Funds and is directly linked to the performance of Islamic Equity Fund managers. Enhanced performance by investment managers in cultivating Islamic Equity Funds is likely to increase the intention to invest in such funds. This study aimed to assess and provide comprehensive information on the performance of Islamic Equity Funds in Indonesia. Quantitative statistical analysis was used to examine the impact of stock selection skills, market timing ability, fund size, fund age, expense ratio, and portfolio turnover on the performance of Islamic Equity Funds. This study utilized annual data from 2015-2020, obtained from the prospectus of each Islamic Equity Fund, Central Bank Indonesia (BI), and the Statistics of Indonesia (BPS). The findings indicated that stock selection skill and expense ratio had a positive and significant effect on the performance of Islamic Equity Funds. However, market timing ability, fund age, and fund size had no significant effect, although the results showed positive values. On the other hand, portfolio turnover had a negative and significant effect on the performance of Islamic Equity Funds. Therefore, it can be inferred that higher stock selection abilities of investment managers lead to better returns, and the expense ratio of an equity fund reflects the costs associated with portfolio management, administration, marketing, and distribution. Originality/Value: This paper addresses the significant issues that arise in Islamic equity funds, which are crucial as investment portfolios, and contributes to a limited body of research in this area. Therefore, gaining insight into the key factors affecting the performance of equity funds can optimize their functionality and attract investors.